PERAN PENDIDIKAN ISLAM DALAM MENUMBUHKAN EMPATI DAN KESADARAN SOSIAL DI ERA INDIVIDUALISME DIGITAL - Hikmah Ramadhani; Nur Khasanah (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2025)
The development of digital technology in the modern era has brought significant changes to the way humans interact, especially among the younger generation. The emergence of a culture of digital individualism has made social relationships increasingly shallow, with virtual connectivity often replacing genuine emotional closeness. In this context, Islamic education plays a crucial role in instilling empathy and building social awareness based on Islamic moral and spiritual teachings. This study aims to examine how Islamic educational institutions contribute to fostering empathy amidst the increasingly strong tide of digital individualism. The study employed qualitative methods with a desk study approach, drawing on relevant literature on Islamic education, educational sociology, and character education from the past five years. The results indicate that Islamic education serves not only to transfer knowledge but also as a means of internalizing humanitarian values ​​such as compassion (rahmah), social responsibility, and justice ('adl). Through the integration of Islamic values ​​into the curriculum, school culture, and teacher role models, educational institutions can strengthen students' empathy and social solidarity. In conclusion, Islamic education plays a vital role as a moral and social bulwark against the impacts of digital individualism, thereby producing a generation that is not only intellectually intelligent but also possesses social and spiritual sensitivity.